(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the scientific literature in a systematic way to analyze the effect of NMES on muscle strength gain and motor performance in the elderly. The bibliographic survey was carried out through publications indexed in the database of the Virtual Health Library, Scientific Electronic Library Online, Medical Literature Analysis and Retrieval System Online, US National Library of Medicine National Institutes of Health and Physiotherapy evidence database. The search was carried out using the descriptors in Portuguese and English: “Electrical Stimulation Therapy”, “muscle strength”, “motor performance” and “elderly”. To organize the study, the criteria of the PRISMA systematic review (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) were followed. After evaluation, five articles were selected that met the inclusion criteria. Several studies have shown data that provide evidence that neuromuscular electrostimulation is a safe method to combat muscle decline in the elderly, as well as prevents the loss of muscle strength and provides its increase. This review was conclusive regarding the effectiveness of NMES, as it demonstrated that there is effectively an increase in the strength of MMII and improvement in motor performance after an NMES protocol in the elderly, even with great divergence in parameters and intervention time.